Curating the Sacred: Exhibiting Buddhism at the World Museum Liverpool - Tythacott, Louise (Buddhist Studies Review, 2017)
This article explores issues involved in representing Buddhism in museums, drawing on the author’s experience of curating the Buddhism display at the World Museum Liverpool. It is concerned with processes of de-contextualization and re-contextualization, focussing on whether sacred images become divested of their religious functions once they enter a museum or if, instead, the gallery can be considered an alternative arena for contemplation. The article begins by reviewing the literature on museums and the sacred. It discusses the lack of concern historically for religion in museums, noting how sacred objects have tended to be ‘secularized’ in exhibitionary contexts. It then examines the Buddhism display at the World Museum Liverpool, part of the permanent World Cultures gallery which opened in 2005, with its reconstructions of a shrine, an altar and a protective chapel — this is a museological environment which deliberately evokes the atmosphere of a temple.